Application of the Thermodynamic System to Analyze the Relationship of the Money Amount Circulating Against Inflation. (March 2020) - Kartono, A; Yufida, A; Wahyudi, S T; Irmansyah,
Abstract: Based on an analogy between thermodynamics and economic theories, one of many economic problems can be represented by the ideal gas equation. Scientists have considered modifying the formulae from an ideal gas in thermodynamic principle to be applied to economic problems. An ideal gas is composed of many molecules. This ideal gas with the outside environment limited by the boundary system. Therefore, this gas is only contained in a volume so that this gas will exert pressure on the walls of the system. The gas molecules will vibrate and move about faster so they will increase their rate of exchange of kinetic energy. Since this gas also accumulates internal energy, an increase in temperature will be generated in this process so pressure and volume potentially increasing too. An equation of ideal gas has a similar structure to the equation of an economic system. Many molecules are assumed as monetary carriers or holders of value, equivalent in size to units of currency. The relationship of the system with the outside environment is that the value held by carriers or holders can be exchanged for goods and services at the boundary system at price (as pressure) and volume over a period of time, according to an index (or a degree of a scale) of trading value (as temperature) with which they can do this over that period. The objective of this study was to obtain inflation index value ( m ), to find out the inflation rate in Indonesia in that year and to analyze the causes and solutions for the better in the following year. The economic analysis of inflation is applied to the ideal gas theory. The parameters needed to be the money supply, the price index, and the speed of the money supply. The calculation and analysis with this ideal gas equation showed that all parameters used were affecting each other. The data from the last ten years showed that there was a significant change in the value of elasticity index value ( n ) for 4 times. All changes were in different time frames. Based on the ideal gas theory, a good value of n was a value of n that is less than or equal to one.